PEMBEKUAN SEMEN LELE DUMBO (Clarias Gariepinus BURCHELL 1822) SEBAGAI MODEL KRIOPRESERVASI SEMEN IKAN - Lutfi Lutfi (Jurnal Natural, 2010)
Effect of four types of diluentss and four concentration of DMSO (5%, 10%, 15% and 20%) against the motility of African catfish sperm were evaluated after storage at freezing temperatures. The steps in preparation the 16 treatments combination of the diluents are preparation of diluents, mixing diluents with DMSO, packing of semen into 0.3-ml straw, equilibration of semen at 4 °C for 30 minutes, freezing of semen in nitrogen vapor liquid at a height of 6.5 cm for 10 minutes, and subsequently storage of semen in liquid nitrogen (-196 0C) for further analysis of post-thawing motility (PTM). The result showed that the highest level of motility of spermatozoa was in treatment P1D15 (45.7 ± 4.3%) and the lowest was in treatment P2D20 (14.5 ± 13.2%). The best diluent in this observation was diluents containing NaCl, KCl, CaCl2 and NaHCO3. The best concentration was DMSO 15%. While the best interaction between the concentration of DMSO diluents is P1D15 treatments containing NaCl, KCl, CaCl 2 and NaHCO3 with a combination of 15% DMSO concentration. The conclusion of the research is that diluents containing NaCl, KCl, CaCl2 and NaHCO3 with a combination of 15% DMSO concentration can be used in cryopreservation of African catfish semen.